Electrochemical and structural properties of binder-free iron-based bifunctional catalyst for aqueous Zinc-Oxygen batteries - Jorge González-Morales; Mario Aparicio; Nataly Carolina Rosero-Navarro; Franco M. Zanotto; Alejandro A. Franco; Jadra Mosa (Open Ceramics)
Global warming necessitates efficient new batteries, with Zn-O2 batteries standing out due to their high theoretical energy density, safety, and long cycle life, making them ideal for large-scale use. However, their industrial application faces challenges such as rapid energy density decline after initial cycles, limited cathode efficiency, and high overpotential between discharge and charge. This study focuses on synthesizing and characterizing ceramic iron compounds as catalysts for the cathode of Zn-O2 aqueous batteries. The findings revealed that obtained catalysts presented surface active areas beyond 220 m2/g after calcination at 800 °C, which removed organic templates. Various thermal treatments have been analysed to measure their impact on the final product. XRD, FTIR, and Raman spectroscopy confirmed sample nitridation, while SEM showed macro–meso-porosity. The electrochemical evaluation demonstrated a significant enhancement in the material's catalytic properties for ORR/OER in alkaline Zn-O2 batteries, surpassing 140 h of satable cyling with catalytic activity for ORR and OER. This improvement, coupled with optimized electrode design, resulted in a substantial increase in the batteries' operational life, achieving stable cycling for over 120 h.